(a-b) = 0
In this problem, division by zero is not allowed, and thus your math is incorrect.
2007-01-07 18:34:31
·
answer #1
·
answered by Patrick M 2
·
0⤊
0⤋
Here is the solution
Line1--> If a=1 and b=1 then a = b
Line2--> Multiply by a* then a* = a*b
Line3--> Subtract b* then a* - b* = ab - b*
Line4--> Now since a=b so a*=b*
Putting these values in Line 3 we get
Line5-->a*-a*=aa-a*
Now when a=1 and b=1, line 5 becomes
Line6--> 0=0 hence proved that you are wrong !!
:) :)
2007-01-07 18:41:55
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
weird! its quite simple. a-b is 1-1 and 1-1 is 0. You CANNOT divide by zero!
2007-01-07 18:37:34
·
answer #3
·
answered by Az 3
·
1⤊
0⤋
if a=b
the a-b=0
to follow your math,
a* - b* = ab - b*
factor: (a+b)(a-b) = b(a-b)
compared to a-b = 0, then
(a+b)(0) = b(0)
0 = 0
besides, in math, different letters mean different value, so the "if a=1 and b=1" part is not mathematically valid.
2007-01-07 18:47:04
·
answer #4
·
answered by BryanB 4
·
0⤊
0⤋
it is simple.
(a + b)(a -b) = b(a - b)
which is mean:
(a + b)( 0 ) = b( 0 )
you should remember two laws:
1. 0 * (anything) = 0
2. (anything) ^ 0 = 1
( maybe you ask me:
what about this one:
0 ^ 0 = ?
or:
(infinity) * 0 = ?
who knows? maybe you find out some day.)
2007-01-07 19:49:03
·
answer #5
·
answered by Shahin H 1
·
0⤊
0⤋
you would have a zero in your solution and you cannot divide by a 0 so you are wrong
2007-01-08 02:13:09
·
answer #6
·
answered by David C 2
·
0⤊
0⤋
(a + b)(a - b) = b(a - b)
Now if a=b=1, then
(a+b)*0 = b*0
Anything * 0 = anything else * 0. It all falls apart.
2007-01-07 18:36:35
·
answer #7
·
answered by miket 4
·
0⤊
0⤋
2 is the loneliest number since the number one
2007-01-07 18:39:05
·
answer #8
·
answered by Chris B 4
·
0⤊
0⤋
multiply by a:
a^2=ab
u got mistake here
2007-01-07 20:53:43
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
Yeah, its called marriage.
2007-01-07 18:37:08
·
answer #10
·
answered by TheSilverBeetles 4
·
2⤊
0⤋